2020
DOI: 10.1021/acsomega.9b03309
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a SnO2-Based Hydroelectric Cell for Green Energy Production

Abstract: The generation of electricity by dissociating water into H 3 O + and OH − ions through a hydroelectric cell (HEC) without liberating any toxic waste has achieved a groundbreaking feat. Nanoporous magnesium-doped SnO 2 and cobalt-doped SnO 2 materials have been prepared via a novel sol−gel method. The X-ray diffraction patterns of Mg-doped SnO 2 and Co-doped SnO 2 completely match with those of pure SnO 2 , which confirms the interstitial substitution of Mg and Co in the pristine SnO 2 . The results shown by Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It is explicitly from the comparative analysis that current density of HEC is improving with short span of time. 19,41,78 The graphene oxide-based battery from electrochemical method yielded maximum power output of 2 μW in the presence of electrolyte. 15 The cement matrix based composite battery generates voltage of 0.72 V with current per unit area of 0.0038 mA/cm 2 .…”
Section: Comparative Performance Of Hec With Water Based Other Enermentioning
confidence: 99%
See 3 more Smart Citations
“…It is explicitly from the comparative analysis that current density of HEC is improving with short span of time. 19,41,78 The graphene oxide-based battery from electrochemical method yielded maximum power output of 2 μW in the presence of electrolyte. 15 The cement matrix based composite battery generates voltage of 0.72 V with current per unit area of 0.0038 mA/cm 2 .…”
Section: Comparative Performance Of Hec With Water Based Other Enermentioning
confidence: 99%
“…Different types of water based energy sources using external energy have been explored and a comparison of correlation between voltage and current densities is represented by bar chart in Figure 8A,B. It is explicitly from the comparative analysis that current density of HEC is improving with short span of time 19,41,78 . The graphene oxide‐based battery from electrochemical method yielded maximum power output of 2 μW in the presence of electrolyte 15 .…”
Section: Factors Affecting the Performance Of Hecmentioning
confidence: 99%
See 2 more Smart Citations
“…The device adsorbs and spontaneously chemi-dissociates water molecules on defective material surfaces into H + and OH – ions at room temperature. Nanopores in the cell material act as trapping centers for hopping protons, which generate a high electric potential inside the nanopore and sustained splitting of physisorbed water molecules. ,− It has been observed that surface defect states, such as oxygen vacancies, interstitials, and unsaturated surface bonds, enhance active sites for water molecule attraction and the chemi-dissociation reaction. , Doping of metal ions has been found to be very effective to enhance the defect concentration, which improved the current generation by SnO 2 -based HEC . Antimony (Sb) doping has been reported to largely increase the surface area and defect concentration in SnO 2 nanoparticles. It occupies Sn 4+ sites in the rutile structure of SnO 2 , and surface enrichment of Sb 5+ ions has been found to be responsible for increased surface conductivity .…”
Section: Introductionmentioning
confidence: 99%